Monoclonal antibodies (update): CD20, rituximab (Hematology Meeting Reports, 2009)
Without any doubt, in the past 10 years Rituximab has caused a breakthrough in the prognosis of patients with both indolent and aggressive NHL. After it was shown that Rituximab as a single agent had significant activity in concert with a most favourable toxicity profile, the combination with appropriate chemotherapy showed not only an improved response rate and progression free survival, but – most strikingly – a significantly better overall survival. This has been particularly impressive in patients with advanced follicular NHL, in which group OS could not be improved during the past 30 years despite many attempts employing different treatment modalities (Marcus and Hagenbeek, 2007).